Socio-demographic factors influencing practice and awareness of exclusive breastfeeding benefits among women of reproductive age attending maternal and child health clinic in tudor sub county hospital - Machila, Consolata Mandi; Karonjo, Jane; Mogere, Domnic; Kariuku, Peterson (International Journal Of Community Medicine And Public Health, 2021)
Background: Knowledge of exclusive breastfeeding (EBF) among women is essential when promoting optimal breastfeeding practices. Breastfeeding is recommended for the first six months of life and continuation of breastfeeding and adequate complementary foods for up to two years of age or beyond. Methods: A descriptive cross-sectional study design was used. This study utilized a mixed method approach (qualitative and quantitative). Results: Four socio-demographic factors were found to be influencing the practice of exclusive breastfeeding. Those include child gender, level of education, marital status and parity. Two socio-demographic factors were found to influence awareness of the benefits of EBF. Those are Level of education and Occupation. Conclusions: The government should improve on the level of education of women in the area. Increase in number of educated women.